Application of The Student Team Achievement Division Model to Improve Learning Outcomes of Class V Angle Material - Jefrianus Putra Zebua; Karina Nurohma Dayani; Anisa Saskia Putri; itsna Zulfatul Tsaniyah; Esteni Sallah; Neni Novitasar Novitasari (Yayasan Citra Dharma Cindekia, 2026)
This study aims to improve students’ understanding of multiplication concepts through the application of a concrete learning model. The research employed a Classroom Action Research design conducted in two cycles, involving 21 third-grade elementary school students. Data were collected through observation, tests, and interviews.The findings indicate a significant improvement in students’ conceptual understanding of multiplication. The average test score increased from 60.2 in Cycle I to 82.5 in Cycle II. Additionally, the percentage of students achieving mastery learning improved from 52% to 90%, meeting the predetermined success criteria. Qualitatively, students showed increased engagement, participation, and confidence during the learning process. The use of concrete objects in the learning model helped students understand abstract mathematical concepts more effectively and created a more interactive and meaningful learning environment. Therefore, the concrete learning model is effective in improving students’ understanding of multiplication concepts and can be used as an alternative instructional model in elementary mathematics learning.